2020
DOI: 10.36380/scil.2020.wvj17
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile and Enzymatic Activities of Frozen Buck Sperm Supplemented with Melatonin in Cold and Hot Temperatures.

Abstract: This study was carried out to improve the freezability of buck semen using two different types of cryoprotectants supplemented with melatonin as antioxidant in cold and hot temperature of breeding season. Ejaculates from four mature Egyptian baladi bucks were pooled after collection. Semen was extended with Tris-fructose-citric containing egg yolk using glycerol and dimethyl sulfoxide supplemented with two doses of melatonin (10-6 M and 10-3 M) in addition to control group. Types of motility as well as velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…In line with the previous findings, melatoninsupplemented male goat semen showed enhanced total and progressive sperm motility values for CASA parameters [30]. It should be noted that the inclusion of antioxidants (L, M, and S) is necessary to maintain the viability and quality of semen following cryopreservation [27,28,29].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with the previous findings, melatoninsupplemented male goat semen showed enhanced total and progressive sperm motility values for CASA parameters [30]. It should be noted that the inclusion of antioxidants (L, M, and S) is necessary to maintain the viability and quality of semen following cryopreservation [27,28,29].…”
Section: Discussionsupporting
confidence: 84%
“…To maintain semen quality and viability following cryopreservation, antioxidant addition (L, M, and S) is necessary [27,28,29] . The present study showed an increase in total and progressive motility in semen groups supplemented with various antioxidants, which is consistent with earlier investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrated up-regulation of two mitochondrial transcripts (CPT2 and ATP5F1A) that enhance metabolic activity of spermatozoa in semen groups supplemented with Cys, LC + M, LC + Cys and M + Cys. Similarly, up-regulation of these two genes was reported in ram semen that showed enhancement in post-thaw sperm motility (Dessouki et al, 2020). In a microarray study, transcripts associated with keeping haemostasis of mitochondrial membrane potential were upregulated in high-fertile bulls (Madeja et al, 2021;Saraf et al, 2021).…”
Section: Nrf2mentioning
confidence: 65%
“…Cryopreservation process can also reduce mRNA expression levels of five vital antioxidant enzymes (CAT, Cu/Zn-SOD, Mn-SOD, GPx, and GR) in mammalian sperm [ 13 , 14 , 15 ]. Imbalance in antioxidant defense might be responsible for mitochondria-oriented apoptosis [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%